Pre-Implant Immune Status is Associated with Infection Risk After Left Ventricular Assist Device Implantation - Dieterlen MT; Messer EK; Klaeske K; Sieg F; Eifert S; Haunschild J; Jawad K; Saeed D; Dashkevich A; Borger MA (Dove Medical Press, 2024)
Maja-Theresa Dieterlen,* Eva Katharina Messer,* Kristin Klaeske, Franz Sieg, Sandra Eifert, Josephina Haunschild, Khalil Jawad, Diyar Saeed, Alexey Dashkevich,* Michael Andrew Borger* University Clinic of Cardiac Surgery, Leipzig Heart Center, HELIOS Clinic, Leipzig, Germany*These authors contributed equally to this workCorrespondence: Maja-Theresa Dieterlen, University Department for Cardiac Surgery, Heart Center Leipzig, University Hospital, HELIOS Clinic, Strümpellstraße 39, Leipzig, 04289, Germany, Tel +49 - 341 865 1651, Fax +49 - 341 865 1452, Email mdieterlen@web.dePurpose: Infection is the most common complication after left ventricular assist device (LVAD) implantation. The immune status of LVAD patients is relevant for the incidence and severity of infection, but it is unknown if there is a predisposing immune status prior to LVAD implantation that contributes to an increased risk for infection in the post-implant period. We analyzed the pre-LVAD immune status in patients with infection within 3 months after LVAD implantation in comparison to infection-free patients.Patients and Methods: Fifty-four consecutive LVAD patients were included in this study. According to their infectious history in the first 3 months after LVAD implantation, these patients were grouped into an infection (n=23) and an infection-free group (n=31). Pre-LVAD blood samples were obtained for flow cytometric analysis of immunological parameters including B cells, subsets of T, dendritic and natural killer cells. Patient-specific, clinical and laboratory data were recorded.Results: Blood count analysis prior to LVAD implantation showed comparable counts of erythrocytes (p=0.19), platelets (p=0.33) and leukocytes (p=0.50) between patients with infection and infection-free patients in the post-implant period. Patients with infection in the first 3 months after LVAD implantation had lower concentrations of lymphocytes (p=0.02). Forty percent of the patients with infection showed more often pre-LVAD neutrophil-to-lymphocyte ratios (NLR) > 7 than patients without infection in the first 3 months after LVAD implantation (14%, p=0.05). Patients with infection already had lower percentages of CD3+ T cells (p=0.03), CD19+ B cells (p< 0.01), BDCA2+ pDCs (p=0.03) and BDCA4+ plasmacytoid DCs (pDCs) (p=0.05) prior to LVAD implantation than infection-free patients.Conclusion: Our results demonstrated that patients with infection in the early post-implant period showed lower concentrations of lymphocytes, especially of CD3+ T cells and CD19+ B cells, decreased percentages of BDCA2+ and BDCA4+ pDCs, and had more often NLRs > 7 indicating moderate-to-severe inflammation. Thus, we identified specific immunological changes pre-LVAD that could help to identify patients at risk for infection in the early post-implant period.Keywords: LVAD, immune system, T cells, B cells, plasmacytoid dendritic cells, neutrophil-lymphocyte ratio